Public Satisfaction Survey for Improving The Quality of Public Services in The DPMPTSP Jambi Province - ASTI HAKENI HARKENI; Vinni Aprilianti (Khazanah Intelektual, 2022)
Research has been carried out on a Community Satisfaction Survey (SKM) at the Investment Service and One Stop Integrated Services (DPMPTSP) Jambi Province Semester II in 2021. The survey was carried out as an effort to improve the quality of public services in accordance with PERMENPAN RB RI Number 14 of 2017 concerning Guidelines for Compiling a Satisfaction Survey Community Public Service Implementation Unit. SKM is one of the tools used by the public service unit to evaluate the performance of the services carried out by the unit, in this case the Jambi Province Investment and One Stop Service (DPMPTSP). This study uses a descriptive approach with mixed methods and research instruments, namely the distribution of online and offline questionnaires, review of documentation and observations. The population is people who have received licensing services in Jambi Province and data analysis using univariate and bivariate analysis. The survey was conducted based on Permenpan RB Number 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey using 9 indicators in the Likert scale interval range of 1-4. The results obtained that the average value of the Community Satisfaction Survey in the Jambi Province DPMPTSP in 2021 for the second semester period was the Very category. Good (A) with a score of 91.64. Most of the relationships between elements have been correlated, from 36 relationships there were 27 relationships or 75% had correlations while 9 (nine) relationships were not significant so they had no correlation. The priority scale for service improvement is contained in elements of systems, mechanisms, and procedures, elements of completion time, elements of implementing behavior, elements of handling complaints, suggestions and inputs, as well as elements of product specifications for types of services.